APLIKASI TOOLS MANAGEMENT UNTUK MEREDUKSI WAKTU SET UP - Syahputri, Khalida; T, Indah Rizkya (Jurnal Sistem Teknik Industri, 2017)
Generally, furniture industry apply make to order in production systems and job shob (batch) in flow production. To produce a number of products with a uniform design of the required tools in the form of jig. Problems occurred at one of the furniture industry is the high sets up time due completion of the jig for use. Damaged Jigs, no precision, and unavailable jigs become the main reason for set up time be longer. The impact of time disrupted production and production targets are not reached. These problems can be overcome with management tools so that the tool/jig is ready for use in times of need. Using the tool management long setup time can be reduced because equipment is not ready for use and storage techniques by replacing the jig into removing the clamp handle can minimize the need of storage space. The settings storage location having regard to the level of usage can accelerate the process of supply to jig machining settings that the setup of jig include storage layout using the principles of popularity, making the procedure management of the jig in the room. The results obtained that with tool management setup time can be reduced to 61.17%.